The prime hurdles to a democratic political transition in Syria : a combination of the innate sectarian cleavages and vested foreign interests? - Maeresera, Sadiki; Matedza, Babra; Nyakabau, Karen; Rugeje, Engelbert (Adonis and Abbey Publishers Ltd, 2021)
A civil war in Syria between the regime of Bashar al-Assad against the different local and international anti-regime actors has devastating effects on human lives. As the attempted democratic transition turned into a prolonged civil war, increased foreign interest and innate sectarian cleavages within the country hindered any possibilities of a democratic transition. As the growing geopolitical tensions in Syria intensify, wrestling for power and influence in Syria among individual nation-states have continuously arisen. Against this background, this paper examines the extent to which innate sectarian cleavages and vested foreign interests have been the prime hurdles to a democratic political transition. To arrive at the conclusion of this paper, the origins of the democratic political transition would be traced with a view to comprehend the political and security situation in Syria before and after the transition. The basis of vested foreign interests and sectarianism in Syrian democratic transition will be juxtaposed from the context of realism and power politics theoretical foundations in order to examine the influence of these two variables in the problem under scrutiny.